Characterization and Explanation of Primary, Return and Onward Interprovincial Migration: Canada, 1976-86 - Newbold, Bruce Kenneth (My University, 1994)
Using data from the Public Use Sample files of the 1981 and 1986 Canadian censuses, this thesis sets out to characterize and explain primary (migration from the province of birth), return (migration back to the province of birth following an initial migration) and onward (migration to a province other than the province of birth following an initial migration) interprovincial migration within Canada for the 1976-81 and 1981-86 periods.
Three major themes are developed and expanded over the course of the thesis. The first theme is one of characterization. In order to study the propensities of in- and outmigration, appropriate in- and outmigration rates are computed (Long, 1988; Rogers and Belanger, 1990). The major finding is that the Canadian migration patterns are similar to those observed in the United States.
The second theme is the explanation of return and onward migration amongst non-natives (those whose province of residence was different from their province of birth) aged 22-44 within Canada by applying a three-level nested logit model to the 1976-81 micro data. Research has tended to take either a macro-adjustment or micro-behavioral stance in modeling migration flows, but the complementary frameworks suggest the need for an integrative approach incorporating structural-institutional forces and personal factors. Important factors include mother tongue, level of education, age and family type. Influential provincial attributes include economic variables, distance and cultural similarity. The main finding is that return migrants also responded to interprovincial variations in economic opportunities in a rational way.
The final theme is the temporal analysis of primary, return and onward migration through the economic boom of 1976-81 and economic bust of 1981-86. Relative to return migration, primary and onward migration became less important during the period of economic bust, although migration became less important during the period of economic bust, although migration selectively with respect to personal factors remained basically the same. In making migration decisions, non-natives continued to respond to the spatial variation in economic opportunities so that the spatial patterns of migration changed in response to the changing spatial economy.
Keywords: Geography; Geography